The influence of specific cognitive training in virtual reality on the inhibition of elite young ice hockey players - Heilmann, F.; Schubert, T. (Frontiers in Sports and Active Living, 2025)
Introduction: Executive functions (EFs) such as inhibition skills are crucial in sports, particularly in game sports, as they facilitate rapid decision-making, impulse control, and effective reactions to unforeseen situations. This study investigates the influence of specific cognitive training (CT) in virtual reality (VR) on inhibition in young ice hockey players compared to an individual technical training session. The potential implications of this research are significant, as it could lead to the development of new training methods to improve sports performance.